An observational analysis of kicker-goalkeeper interaction in penalties between national football teams in international competitions - Barbero, J. R.; Lapresa, D.; Arana, J.; Anguera, M. T. (International Journal of Performance Analysis in Sport, 2023)
An observation instrument was designed to analyse the interaction between the kicker and goalkeeper in a penalty kick, which allows to obtain relevant information in order to predict the direction of the kick. To fulfil this aim, an analysis was carried out of the interaction between kickers and goalkeepers in penalties taken in the following international team competitions: European Football Championship, Africa Cup of Nations, Copa América, AFC Asian Cup and Concacaf Gold Cup. Intra and inter-observer reliability was guaranteed using Cohen's Kappa coefficient. Evidence was produced of generalisation accuracy in the observation sample and of the validity of the observation instrument. The results obtained provide relevant information regarding the zone -or sector- of the goal towards which the kick is aimed, from the information contained: in the contextual dimensions "competition", "match time", "match score" and "match result"; and in the dimensions that make up the diachronic structure of the observation instrument -"start of kicker`s run-up in relation to the ball", "goalkeeper actions prior to the kick", "movements in kicker`s run-up", "length of kicker`s run-up", "speed of kicker`s run-up", "direction of kicker`s supporting foot", "position of opposite arm to kicker`s kicking foot" and "contact surface".